Reduced gap junction coupling amplifies the effects of cardiomyocyte variability and destabilizes the heartbeat - Karoline Horgmo Jæger; William E. Louch; Aslak Tveito (Physiological Reports)
Abstract Cardiomyocytes exhibit significant cell‐to‐cell variability due to differences in protein expression and post‐translational modifications in the cell membrane and the intracellular machinery. Resulting variability in action potential propagation and configuration is proposed to promote arrhythmia. However, such effects may be suppressed by tight electrical coupling of cells in the healthy heart, but not during pathological conditions where gap junction function is impaired. To investigate this, we employed a cell‐based mathematical model of cardiac electrophysiology, in which we systematically modified properties of individual cells and intercellular electrical connectivity (gap junctions). Despite the inclusion of marked variation in properties between cells, we observed electrical homogeneity when cells were well coupled. In contrast, lower and/or more variable gap junction connectivity resulted in nonhomogeneous action potential configuration and irregular timing of the depolarizing and repolarizing electrical wavefronts. Pro‐arrhythmic early after depolarizations also occurred under these conditions. These effects were effectively dampened in highly coupled cells. Nevertheless, differences in calcium homeostasis were not negated by gap junction coupling, indicating a limit to which electrical connections can homogenize mechanical function. Our findings underscore the critical role of intercellular coupling in maintaining cardiac stability and highlight the importance of studying cardiomyocytes within a syncytium rather than in isolation.